Are institutional deliveries promoted by Janani Suraksha Yojana in a district of West Bengal, India? - Tanmay Kanti Panja; Dipta Kanti Mukhopadhyay; Nirmalya Sinha; Asit Baran Saren; Apurba Sinhababu; Akhil Bandhu Biswas (Wolters Kluwer Medknow Publications, 2012)
'Janani Suraksha Yojana (JSY)' was implemented in India to promote institutional deliveries among the poorer section of the society. A cross-sectional study was conducted in Bankura district among 324 women who delivered in last 12 months selected through 40 cluster technique to find out institutional delivery rate, utilization of JSY during antenatal period and relation between cash benefit under JSY during antenatal period and institutional delivery. Overall institutional delivery rate was 73.1% and utilization of JSY among eligible women was 50.5%. Institutional delivery (84.0%), consumption of 100 iron-folic acid tablets (46.0%) and three or more antenatal check-ups (91.0%) were better in women who received financial assistance from JSY during antenatal period than other women. After adjustment for socio-demographic factors, JSY utilization came out to be significantly (P=0.031) associated with institutional deliveries. The study showed that cash incentive under JSY in antenatal period had positive association on institutional deliveries.